New insights into ion channel‐dependent signalling during left‐right patterning. (13th June 2019) - Tajhya, Rajeev; Delling, Markus
Abstract: The left‐right organizer (LRO) in the mouse consists of pit cells within the depression, located at the end of the developing notochord, also known as the embryonic node and crown cells lining the outer periphery of the node. Cilia on pit cells are posteriorly tilted, rotate clockwise and generate leftward fluid flow. Primary cilia on crown cells are required to interpret the directionality of fluid movement and initiate flow‐dependent gene transcription. Crown cells express PC1‐L1 and PC2, which may form a heteromeric polycystin channel complex on primary cilia. It is still only poorly understood how fluid flow activates the ciliary polycystin complex. Besides polycystin channels voltage gated channels like HCN4 and KCNQ1 have been implicated in establishing asymmetry. How this electrical network of ion channels initiates left‐sided signalling cascades and differential gene expression is currently only poorly defined. Abstract : Motile cilia on pit cells (blue) generate a leftward directed flow within the LRO. Primary cilia on crown cells (brown) lining the outer perimeter of the node presumably function as flow detectors as they are required to initiate left‐sided asymmetric gene expression (insert). The initial asymmetry generated within the LRO spreads out into the surrounding mesoderm (green) and thus defines the left side of the embryo. The polycystin members PC1‐L1 and PC2 reside on primary cilia of crown cells and genetic evidence strongly suggests that this ion channel complex is required for flow‐induced gene expression (insert). Yet the activation mechanism by which this ion channel complex is activated by flow on primary cilia still remains poorly understood. Besides ciliary polycystin channels other membrane localized voltage‐gated channels (insert) have been implicated in establishing asymmetry, suggesting that they may function as signal amplifiers.